Tantangan dan Strategi Pengembangan Karakter Siswa Melalui Proyek Penguatan Profil Pelajar Pancasila (P5) di SDN 12 Karang Tengah - Rahman, Rifan Maulana; Magdalena, Ina; Huliatunisa, Yayah (Journal of Moral and Civic Education, 2025)
Moral degradation among students is a crucial issue in education, demanding the implementation of a character-oriented curriculum, as embodied in the “Curriculum Merdeka” with a focus on the Pancasila Student Profile (P5). This article aims to examine in-depth the implementation of the Curriculum Merdeka in one of the pioneering schools, SDN 12 Karang Tengah. This study uses a descriptive qualitative method, with data collected through observation, interviews, and documentation analysis. The implementation of the curriculum in this school is analyzed based on four stages: preparation, planning, implementation, and evaluation, and is linked to the three dimensions of Thomas Lickona's moral character: moral knowing, moral loving, and moral doing. The results show that the implementation of P5 is generally effective, although it still faces obstacles, especially related to limited supporting facilities. The main limitation of this study is the scope of the study which only focuses on one school in a specific area, so generalization of the findings needs to be done carefully.